Uma genealogia das mulheres no sistema publicitário brasileiro - Silva, Carolina Minuzzi Murari da (2020)
This research aims to study gender issues and power relations in the advertising system. For this, we outline the following reseach problem: How do power relations dimensioned in gender roles affect women’s professional practices in the Brazilian advertising system? Regarding the the general objective, we want to: analyze, through the genealogical procedure, how the trajectoties take place and how the practices of women are configured in the Brazilian adversiting system. Still, in relation to the specific objectives: a) Draw up a timeline for the insertion of women in the advertising system; b) Analyse gender issues and power relations within the scope of advertising production; c) Draw the main stereatypes of women in the advertising product, between 1970 until 2019, in Brazil, from Hall (1997). For this, at first, we are focused on analyzing the instance of advertising production, and, for that, we start from the interviews with four advertises: Heloísa, Lívia, Fernanda and Júlia, and more in the document avaliable on the intetnet about the professional Hilda Schützer. Attentive to this subject knowledge (FOUCAULT, 1986) we reconstructed the history of advertising system from the feminine, taking into consideration tow procedures of Foucault’s discourse (2014): the exclusion and control, and also, we brought the four aspects the make uo the gender as an anyticalcategory by Scott (1995): culturally available symbols, normative concepts, social institutions and organizations and subjective identity. In the second part os our genealogy, wich is focused on the advertising product, we traced the main stereotypes found in advertising between the 1970s and 2019, starting with Hall (1997). For this, we divided our efforts in two phases. In order to map advertising advertisements during these years, we also decided to map advertising surveys that intersect gender issues, to take advantage of the advertisements in these surveys. So, the first phase of the second movement os our genealogy relies on the mapping of advertising surveys that are intersected with the gender theme between the years 1972 to 2019. We started frm the thesis of Tomazetti (2019) and Sucupira Plataform, and found 57 surveys. Thirteen surveys were selected, as they were available online and have advertisements with representations of women. Also, within the selected surveys, we removed 42 advertisements to be analyzed in relation to the represetations. We found 7 stereotypes of women between the 1970s and 2019 in advertisements in Brazil: girl- woman; mother woman; woman housewife; working woman; sexy woman; modern-woman, empowered woman. The theoretical bases that helped us in the analysis rely on the concepto f advertising by Casaqui (2011), the practies of contesting advertisements in Wottrich (2017), the theory os empowerment by Berth (2019), the reflections o nus women from of the feminist movement, and mainly the issues worl, from Oliveira-Cruz (2016). Thus, we consider thet women in the advertising system strive to reconcilie issues in the professional and domestic environments, such as moral and sex harassment, lack of legitimacy of speech and performace and motherhood.